Recent advances on cyclodepsipeptides: biologically active compounds for drug research - Liu, Si-Xuan; Ou-Yang, Si-Yi; Lu, Yong-Fu; Guo, Chun-Lin; Dai, Si-Yang; Li, Chang; Yu, Tian-Yi; Pei, Yue-Hu (Frontiers in Microbiology, 2023)
Cyclodepsipeptides are a large family of peptide-related natural products consisting of hydroxy and amino acids linked by amide and ester bonds. A number of cyclodepsipeptides have been isolated and characterized from fungi and bacteria. Most of them showed antitumor, antifungal, antiviral, and antimalarial, antitrypanosomal properties. Herein, this review summarizes the recent literatures (2010-2022) on the progress of cyclodepsipeptides from fungi and bacteria except for those of marine origin, in order to enrich our knowledge about their structural features and biological sources.